2017
DOI: 10.5056/jnm17018
|View full text |Cite
|
Sign up to set email alerts
|

The Application of the Rome IV Criteria to Functional Esophagogastroduodenal Disorders in Asia

Abstract: The Rome criteria were amended as Rome IV. For functional esophageal disorders, the exclusion criteria have been more specifically revised based on further understanding of other esophageal disorders, including eosinophilic esophagitis and spastic and hypercontractile motor disorders. Another revised point is the more restrictive definition of gastroesophageal reflux disease, indicating that sensitivity to a physiological reflux burden may be placed more firmly within the functional group. For functional dyspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 41 publications
1
38
0
1
Order By: Relevance
“…12 This has led to the marketing approval of acotiamide in Japan, and the inclusion of acotiamide as a treatment option in ROME IV. 13 Notably, the same trend for improvement of meal-related symptoms has been shown from the European phase IIb trial post-hoc analysis. 14 As there has been no trial conducted in the western population that assesses the long-term safety of acotiamide, the primary objective of this trial was set to evaluate the safety of acotiamide for 1 year, and secondary objectives set to explore the effect of 1 year acotiamide treatment on FD symptoms, QoL and work productivity.…”
Section: Introductionsupporting
confidence: 57%
“…12 This has led to the marketing approval of acotiamide in Japan, and the inclusion of acotiamide as a treatment option in ROME IV. 13 Notably, the same trend for improvement of meal-related symptoms has been shown from the European phase IIb trial post-hoc analysis. 14 As there has been no trial conducted in the western population that assesses the long-term safety of acotiamide, the primary objective of this trial was set to evaluate the safety of acotiamide for 1 year, and secondary objectives set to explore the effect of 1 year acotiamide treatment on FD symptoms, QoL and work productivity.…”
Section: Introductionsupporting
confidence: 57%
“…An investigation on the effect of meal ingestion on symptom generation indicated that not only postprandial fullness and early satiety but also epigastric pain, an epigastric burning sensation, and nausea (not vomiting) may increase after meals [50]. H. pylori infection is considered a possible cause of dyspepsia if successful eradication leads to a sustained resolution of symptoms for more than 6 months, and such status can be termed HpD [52]. Prompt esophagogastroduodenoscopy and H. pylori testing and treatment would be more beneficial, especially in Asia, which has a high prevalence of gastric cancer.…”
Section: Resultsmentioning
confidence: 99%
“…All patients were required to have upper gastrointestinal endoscopy and be Helicobacter pylori negative. Helicobacter pylori infection has been suggested as a possible cause of dyspepsia . Eligible patients could not be taking antidepressant drugs, gastrointestinal motility drugs, antacids, or proton pump inhibitor in the two weeks prior to enrollment and had not been treated with acupuncture in the last month.…”
Section: Methodsmentioning
confidence: 99%